Targeted tPA overexpression in denervated spinal motor neurons promotes stroke recovery in mice. Issue 1 (January 2021) - Gan, Xinling; Chopp, Michael; Xin, Hongqi; Wang, Fengjie; Golembieski, William; Lu, Mei; He, Li; Liu, Zhongwu
Our previous studies demonstrated that axonal remodeling of the corticospinal tract (CST) contributes to neurological recovery after stroke in rodents. The present study employed a novel non-invasive peripheral approach, to over-express tPA in denervated spinal motor neurons via recombinant adeno-associated virus (AAV) intramuscular injection in transgenic mice subjected to permanent middle cerebral artery occlusion (MCAo), in which the CST axons are specifically and completely labeled with yellow fluorescent protein (YFP). One day after surgery, mice were randomly selected to receive saline, AAV5-RFP, or tPA (1 × 10 10 viral particles) injected into the stroke-impaired forelimb muscles ( n  = 10/group). Functional deficits and recovery were monitored with foot-fault and single pellet reaching tests. At day 28 after MCAo, mice received intramuscular injection of PRV-614-mRFP (1.52 × 10 7 pfu) as above, and were euthanized four days later. Compared with saline or AAV-RFP-treated mice, AAV-tPA significantly enhanced behavioral recovery ( p  < 0.01, both tests), as well as increased CST axonal density in the denervated gray matter of the cervical cord ( p  < 0.001), and RFP-positive pyramidal neurons in both ipsilesional and contralesional cortices ( p  < 0.001). Behavioral outcomes were significantly correlated to neural remodeling ( p  < 0.05). Our results provide a fundamental basis for the development of therapeutic approaches aimed at promoting corticospinal innervation for stroke treatment.